2015
DOI: 10.1002/ccr3.356
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia and hyperkalemia during magnesium infusion therapy in a pre‐eclamptic patient

Abstract: Key Clinical MessageWe present a case of prominent hypocalcemia and hyperkalemia attributed to magnesium infusion in a preeclamptic patient. Iatrogenic hypermagnesemia is an underrecognized cause of hypocalcemia and hyperkalemia. Our report illustrates the effects of magnesium therapy on serum calcium and potassium, necessitating close electrolytes monitoring when used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
(26 reference statements)
4
18
2
Order By: Relevance
“…In preeclampsia, it has been reported that a decrease glomerular filtration rate (GFR) and renal plasma flow (RPF) possibly decreases sodium delivery to the distal nephron as well as causing decreased potassium secretion [ 19 ]; thus suggesting the possibility of inhibition of urinary potassium excretion prior to administration of magnesium in some preeclamptic women [ 19 ]. An increase in the mean plasma potassium as observed in preeclamptic patients may also possibly be secondary to the effect of magnesium sulphate infusion therapy as Hudali and Takkar [ 20 ] as well as Iglesias et al [ 21 ] reported hypocalcaemia and hyperkalemia during magnesium infusion therapy in preeclamptic patients. It is thought that administration of magnesium in the treatment of preeclampsia possibly reduces the activity of plasma renin and angiotensin converting enzymes resulting in low levels of renin, angiotensinogen, angiotensin II, and aldosterone [ 19 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In preeclampsia, it has been reported that a decrease glomerular filtration rate (GFR) and renal plasma flow (RPF) possibly decreases sodium delivery to the distal nephron as well as causing decreased potassium secretion [ 19 ]; thus suggesting the possibility of inhibition of urinary potassium excretion prior to administration of magnesium in some preeclamptic women [ 19 ]. An increase in the mean plasma potassium as observed in preeclamptic patients may also possibly be secondary to the effect of magnesium sulphate infusion therapy as Hudali and Takkar [ 20 ] as well as Iglesias et al [ 21 ] reported hypocalcaemia and hyperkalemia during magnesium infusion therapy in preeclamptic patients. It is thought that administration of magnesium in the treatment of preeclampsia possibly reduces the activity of plasma renin and angiotensin converting enzymes resulting in low levels of renin, angiotensinogen, angiotensin II, and aldosterone [ 19 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recommended range of total magnesium is between 4.8 and 8.4 mg/dL [8, 9]. It was discovered that most patients had lower total magnesium level than what has been recommended in the guidelines (<4.8 mg/dL).…”
Section: Resultsmentioning
confidence: 99%
“…Many physicians used 1.0 and 1.5 g maintenance dose in their patients’ treatment as it was believed to reduce major side effects, such as hot flashes, blurred vision, and sweating. Interestingly, up to 56.5% of the patients had serum magnesium lower than the recommended therapeutic level (4.8–8.4 mg/dL) [8, 9]. Especially, patients who received 1.0 g/h of magnesium sulfate (88.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadvertent overdose of magnesium can be lethal in dogs and human beings 29 43. Excessive magnesium supplementation can result in hypocalcaemia and hyperkalaemia, the latter due to mechanisms which remain not fully understood 44. Hypermagnesaemia decreases the conductivity of cardiac pacemakers by suppression of calcium channels.…”
Section: Discussionmentioning
confidence: 99%